Non-extraction Tip-Edge appliance management of a moderate Angle Class II division 1 malocclusion commenced in the late mixed dentition - Kift Russell J. (Sciendo, 2000)
This case presentation concerns the correction of a moderate Angle Class II division 1 malocclusion of a patient whose treatment began during the late mixed dentition. Owing to the need to preserve and improve the existing facial aesthetics, treatment was started with a non-extraction approach and, in order to exploit favourable dentofacial growth changes and to avoid the possibility of extraction of teeth, was timed to coincide with the patient's expected adolescent growth spurt. Fixed appliances only were used. Special consideration had to be made for the patient's fractured upper central incisor teeth. An aesthetically pleasing treatment outcome was achieved within the expected time frame for correction. The case shows the successful combination of typical Begg mechanotherapy used during the early stages of treatment and Tip-Edge rectangular archwire mechanotherapy as used for the later and finishing stages.